KEBERADAAN RAMIN (GONYSTYLUS BANCANUS (MIQ.) KURZ) DI KAWASAN HUTAN LINDUNG AMBAWANG KECIL KECAMATAN TELUK PAKEDAI KABUPATEN KUBU RAYA - Astria, Ragil Mega; Muin, Abdurrani; kandar, Is (Universitas Tanjungpura, 2015)
There are the variability of peat swamp forest, one of there domination is Gonystylus bancanus (Miq.) Kurz). Ramin is as one type of constituent of the forest, Ambawang kecil. Currently, its existence endangered due to illegal logging. This research aimed to obtain information about ramin at each level of growth(The number of individuals in the form of availability, level of dominance, and the density of ramin at each level of growth). That information may be the initially to determine the appropiate of silviculture treatment.Â This research used Â the line terraced method, with a width of 20 m, the length of each line 200 m as much as 8 lines, the line spacing of 100 m, and the direction of the scratch line 109 â° 18 ' 55.99 ' ' E. Determination of the initial purposive sampling done on line, based on the consideration of the information field that that location pretty much there is vegetation ramin, the characteristics of the soil with peat moss in marshy waterlogged conditions. Â The results of recearch showed that ramin is dominant in seedlings and saplings of growth level (INP=44,65%, 82,96% respectively). Syzygium sp is dominant in poles of growth level (INP=73,60%) and koompassia malacensis is dominant in tree of growth level (=53,78%). Viewed from its density, ramin have Â fewer number of individuals seedling of growth level (2500/btg/ha) more density mainly for tre of growth level (0,31 btg/ha). Key words : Gonystylus bancanus, seedling, sapling, poles, tree, peat swamp forest